Penyuluhan Kecemasan pada Remaja Siswa/I Kelas X di Sekolah Menengah Atas Kalam Kudus II, Jakarta - Robert Kosasih; Eko Kristanto Kunta Adjie; Daniel Ruslim; Hans Sugiarto; Fernando Nathaniel; Dean Ascha Wijaya; Giovanno Sebastian Yogie (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2023)
Anxiety among adolescents is a growing concern due to its significant impact on their mental and physical well-being. Providing anxiety education in schools can be a crucial step in imparting understanding and stress management strategies to teenagers. This activity aims to conduct an anxiety education program for 10th-grade students at Kalam Kudus II Senior High School, Jakarta. The program is implemented using the PDCA (Plan-Do-Check-Act) method, comprising four stages. The planning stage involves identifying objectives, analyzing needs, planning the content, and scheduling the sessions. Subsequently, in the execution stage, 10th-grade students are given education on anxiety and stress management through presentations and group discussions. Demonstrations and practice of stress management techniques are provided to enable students to apply the skills taught. Upon completing the program, an evaluation is conducted to assess students' understanding of the material and their application of stress management techniques in their daily lives. Feedback from students is collected to evaluate the effectiveness of the activity and identify areas for improvement in future sessions. This initiative is expected to benefit 10th-grade students at SMA Kalam Kudus II, Jakarta, in coping with anxiety and stress during their adolescent years. The education program aims to enhance their understanding of anxiety and equip them with valuable skills for stress management. Ultimately, it is hoped that these teenagers will be better prepared to face life's challenges and achieve improved mental well-being